International agencies and the reform of food subsidies in Egypt after the revolution of 2011 - Di Pietrantonio, Marie (AUC Knowledge Fountain, 2013)
Egypt has a very expensive and extensive food subsidy system representing a heavy burden on the State’s public budget. At the same time, however, these subsidies secure the livelihood of the most vulnerable part of the Egyptian population. While this situation is not sustainable in its current form, no agreement on the extent of the reforms needed and how they should be conducted has yet been reached. This research aims to examine the different viewpoints of stakeholders involved in this issue as well as it intends to investigate the position of different international agencies on food subsidies in general, and in Egypt in particular. Furthermore, does this thesis look at how international agencies influence government decisions on food subsidy reforms and it attempts to determine the other factors of importance in this matter. The analysis is being based on publications from these institutions and on interviews conducted with stakeholders involved in food subsidies reforms. This allowed us to conclude that all actors agree on the fact that the Egyptian food subsidy system needs to be reformed due to its high cost and because it is not sufficiently targeted and suffers important leakages. Regarding the changes that should be introduced, two main positions can be identified; the financial institutions advocate for an immediate switch to a less costly cash transfer system, while the UN organizations, although not against cash transfers, argue that those are not sufficient in protecting the livelihood of the poor in Egypt and are rather in favor of keeping and improving the current systems.